Evaluasi Dampak Perawatan Filter Udara terhadap Performa Mesin Mobil: Tinjauan Empiris di Bengkel Honda Camp Fast Jati Asih - Marysca Shintya Dewi; Rahmat Nur Amin Hidayatullah; Sandy Suryady (JURAL RISET RUMPUN ILMU TEKNIK, 2025)
Air filter maintenanceThis study aims to determine the effect of air filter maintenance on engine lifespan and performance in cars at Honda Camp Fast Jati Asih. The air filter is an important component in the combustion system, as it can influence engine power, fuel efficiency, and engine durability. The research uses a quantitative approach through experiments and case studies, involving cars that regularly undergo air filter maintenance. Data collected includes engine performance before and after maintenance, as well as engine lifespan records during the maintenance period. The results show that regular air filter maintenance can improve engine performance, save fuel, and extend engine life. These findings highlight the importance of air filter maintenance in keeping car engines in good condition.